Simultaneous determination of multiple components in rat plasma by UHPLC-sMRM for pharmacokinetic studies after oral administration of Qingjin Yiqi Granules - Yang, Xiaohua; Chen, Shujing; Du, Kunze; Shang, Ye; Fang, Shiming; Li, Jin; Zhang, Han; Chang, Yanxu (Frontiers in Pharmacology, 2023)
As a Traditional Chinese Medicine (TCM) prescription, Qingjin Yiqi Granules (QJYQ) provides an effective treatment for patients recovering from COVID-19. However, the pharmacokinetics characteristics of the main components of QJYQ in vivo are still unknown. An efficacious ultra-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) was developed and validated for the simultaneous determination of 33 components in rat plasma after oral administration of QJYQ. The plasma samples were precipitated with 400 µL methanol/acetonitrile (1/1, v/v) and analyzed in scheduled multiple reaction monitoring (sMRM) mode. The linear relationship of the 33 components was good (r>0.9928). The lower limit of quantification (LLOQs) for 33 components ranged from 0.4-60.5 ng/mL. The average recoveries and matrix effects of the analytes ranged from 72.9%-115.0% with RSD of 1.4%-15.0%. All inter-day and intra-day precision RSDs were within 15.0%. After oral administration (3.15 g/kg), the validated approach was effectively applied to the pharmacokinetics of main components of QJYQ. Finally, fifteen main constituents of QJYQ with large plasma exposure were obtained, including baicalin, wogonoside, wogonin, apigenin-7-O-glucuronide, verbenalin, isoferulic acid, hesperidin, liquiritin, harpagide, protocatechuic acid, p-Coumaric acid, ferulic acid, sinapic acid, liquiritin apioside and glycyrrhizic acid. The present research lays a foundation for clarifying the therapeutic material basis of QJYQ, and provides a reference for further scientific research and clinical application of QJYQ.